Personal exposure to air pollutants and immune system biomarkers in pregnant women - Marsal, Anouk; Frau, Laurene; Chaperot, Laurence; Amine, Ines; Lyon-Caen, Sarah; Boudier, Anne; Jaffrezo, Jean-Luc; Elazzouzi, Rhabira; Philippat, Claire; Supernant, Karine; Lepeule, Johanna; Quentin, Joane; et al. (Scientific reports, 2025)
The immune function is suspected to play an important role in the health effects of air pollution but it remains poorly investigated in pregnant women. One-week personal measurements of exposure to nitrogen dioxide (NO 2 ), particulate matter with an aerodynamic diameter of ≤ 2.5 µm mass concentration (PM 2.5 ) and PM 2.5 oxidative potential (OP) were assessed in 270 pregnant women from the French cohort SEPAGES. PM filters were analyzed for PM 2.5 OP using the dithiothreitol (DTT) and the ascorbic acid (AA) assays. From a blood sample withdrawn at the end of the exposure measurement week, levels of 29 cytokines and chemokines were measured at baseline and after T cell and dendritic cell activation with phytohemagglutinin (PHA) and resiquimod (R848), respectively. Associations between each air pollutant and each cytokine were assessed using adjusted linear regression models. An increase in NO 2 exposure was associated with higher interleukin 10 (IL-10) and lower PHA-activated tumor necrosis factor (TNF). No association with PM 2.5 concentration was observed, but increased exposure to PM OP AA was associated with lower baseline and R848-activated IL-8 and increased exposure to PM OP DTT was associated with higher PHA-activated IL-17A. Our study provides insights into the relationships between air pollution exposure and immune function among pregnant women.